Thermodynamic design and analysis of movable small scale mixed-refrigerant liquid nitrogen generators. (June 2018) - Wang, H.C.; Guo, H.; Chen, G.F.; Zhao, Y.X.; Dong, X.Q.; Gong, M.Q.; Gao, B.
Highlights: Low cost small scale movable LN2 generator for remote and field users. Low pressure feed gas sources, suiting small commercial air compressors. Simplified configuration and operation of mini cryogenic air separation column. Closed N2 cycle to deliver cooling capacity between flammable MJTR and air/O2 . Utilization of normal refrigeration equipment, various feed gas sources. Abstract: Thermodynamic design and analysis of small scale liquid nitrogen generators based on mixed-refrigerant Joule–Thomson cycle (MR JT) are illustrated in this paper, providing low-cost choices for remote and field users. Bottled pure nitrogen, PSA unit or mini air separation column are utilized in different processes, with feed gases liquefied in the MR JT refrigerators driven by single-stage compressors. Problems in the application of low pressure gas source and mini column are investigated, including column simplification, air liquefaction in flammable MR JT, etc. System exergy analysis is conducted. For pure N2 at 8.0 bar, specific power consumption ( SPC ) of 0.53 kWh L −1 and figure of merit ( FOM ) of 24.46% are achieved. With PSA unit, SPC is 0.85 kWh L −1 . In the process with column, a closed N2 cycle is employed to deliver cooling capacity from flammable mixed-refrigerant to air. Optimal SPC of 0.84 kWh L −1 and FOM of 19.96% are reached.